(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides an overview of the various types of English dictionaries, emphasizing their diversity in scope, size, target users, and functions. It categorizes dictionaries into groups such as historical, concise, learner-oriented, and subject-specific, illustrating how each serves distinct linguistic and educational purposes. By understanding these differences, users can make informed choices about which dictionary best suits their needs, enhancing language acquisition, communication, and academic research.